Esophageal Stenting in the Setting of Malignancy. (8th August 2011) - Martinez, Juan Carlos; Puc, Matthew M.; Quiros, Roderick M.
Abstract : Esophageal cancer is often diagnosed at an advanced stage, with many patients found to have locoregional or metastatic disease at time of diagnosis. Because of this, cure may be unlikely, leading treatment efforts to focus more on symptom palliation and improving patient quality of life. The majority of patients with advanced disease suffer from some degree of dysphagia. Palliative efforts are therefore directed at relieving dysphagia, allowing patients to manage their oropharyngeal secretions, reduce aspiration risk, and maintain caloric intake orally. A variety of endoscopic treatment modalities have been utilized with these objectives in mind, with options determined by the location and size of the tumor, as well as the patient's expected prognosis. In this article, we review the use of endoscopically-placed stents for palliation in patients with advanced esophageal cancer. We discuss the history of stent use in such cases, as well as more recent developments in stent technology. We give an overview of some of the more commonly used stents in practice, discuss the technique of insertion, and survey the short- and long-term outcomes of stent placement.